PELATIHAN MENDELEY DI DAERAH BALONGSARI, KABUPATEN KARAWANG - M. Januar Ibnu Adham,; Dian Hartati,; Sinta Rosalina,; Kelik Wachyudi, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Abstract--In making meaning requires a representative word choice. Likewise, citations and references are required to be thorough in doing so. Need training that can integrate applications that make work like this more accessible. Mendeley is the application chosen to be applied to the participants in Balongsari village because of the function of this tool which is relatively easy to use by the participants. In this training, the service found that most of the participants, in general, did not know Mendeley's application. However, after the training, the participants knew how to use the Mendeley application. In a more specific sense, Mendeley's training is also a form of plagiarism that may arise due to someone's negligence in writing an article.